Human Capital and National Institutional Quality: Are TIMSS, PISA, and National Average IQ Robust Predictors? - Garett Jones; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2014)
Is human capital a robust predictor of good institutions? Using a new institutional quality measure, the International Property Rights Index (IPRI), we find that cognitive skill measures are significant, robust, and large in magnitude. We use two databases of cognitive skills: estimates of national average IQ from Lynn and Vanhanen (2012a) and estimates of cognitive ability based on Programme for International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS) scores estimated by Rindermann et al. (2009). The Rindermann cognitive ability scores estimate mean performance as well as performance at the 5th and 95th percentiles of the national population. National average IQ and the 95th percentile of cognitive ability are both robust predictors of overall institutional quality controlling for legal system, GDP per capita, geography dummies, and years of total schooling. Some possible microfoundations of this relationship are discussed.
Keywords: D73; I20; 330; institutions; human capital; intelligence; PISA